2010
DOI: 10.1007/s10439-010-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Segmentation Approach for Highlighting the Histological Complexity of Human Lung Cancer

Abstract: Lung cancer nodules, particularly adenocarcinoma, contain a complex intermixing of cellular tissue types: incorporating cancer cells, fibroblastic stromal tissue, and inactive fibrosis. Quantitative proportions and distributions of the various tissue types may be insightful for understanding lung cancer growth, classification, and prognostic factors. However, current methods of histological assessment are qualitative and provide limited opportunity to systematically evaluate the relevance of lung nodule cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…Results suggest that the proposed assisted computer system can be a viable alternative to pathologist's scoring in a manner that is more practical and time-efficient. The results obtained agree with previous studies (Galarraga et al, 2012;Pajor et al, 2012;Sieren et al, 2010;Tapias et al, 2013), which also indicated that the automated process greatly reduces the time spent on appraisal, compared with the traditional manual process by effectively transferring the load of the assessment process to the computer.…”
Section: Efficiencysupporting
confidence: 94%
See 1 more Smart Citation
“…Results suggest that the proposed assisted computer system can be a viable alternative to pathologist's scoring in a manner that is more practical and time-efficient. The results obtained agree with previous studies (Galarraga et al, 2012;Pajor et al, 2012;Sieren et al, 2010;Tapias et al, 2013), which also indicated that the automated process greatly reduces the time spent on appraisal, compared with the traditional manual process by effectively transferring the load of the assessment process to the computer.…”
Section: Efficiencysupporting
confidence: 94%
“…As expected, the disparity between the automatic and interactive methods was even smaller (Automated vs. interactive: r Count = 0.924, p Count b 0.001). Accuracy values of the interactive and automated approaches described here are comparable with those of other widely accepted systems (Galarraga et al, 2012;Nielsen et al, 2012;Pajor et al, 2012;Shi et al, 2012;Sieren et al, 2010;Tapias et al, 2013).…”
Section: Accuracysupporting
confidence: 79%
“…Thus, large amounts of data, with tightly controlled cofactors and low population variation, may be achieved, requiring fewer subject numbers for equivalent statistical significance than a human cancer cohort. Furthermore, many cancer types are heterogeneous in content, composed not only of cancerous cells, but also of inflammatory mediators (41), fibrotic stroma (42), necrotic tissue, and complex vascularity (43). Our porcine model does not rely on an immunocompromised host for tumor development, unlike xenograft models (8).…”
Section: Discussionmentioning
confidence: 99%
“…A cell nuclei segmentation algorithm incorporating unsupervised color clustering, morphological operations, and local thresholding has been proposed to distinguish the cancerous and noncancerous areas in histologically stained images and then segment the clustered cell nuclei [3]. K-means clustering is implemented as unsupervised color clustering technique for cell nuclei segmentation in [4]. Another technique that uses contour detection and contour optimization combined with local gradient information and color deconvolution has been used to detect the optimal threshold values for nuclei segmentation [5].…”
Section: Introductionmentioning
confidence: 99%